2015
DOI: 10.1007/s00170-015-8192-x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on abrasive waterjet cutting of CFRP/Ti6Al4V stacks for drilling operations

Abstract: In the present study, CFRP/Ti6Al4V stacks were machined with abrasive water jet using different process parameters in order evaluate the viability of AWJ industrial application as a substitute of conventional drilling. The effect of the stack configuration, the traverse feed rate, the cutting tool (combination of orifice and focusing tube diameter and abrasive mass flow rate), and the pressure over the kerf profile, taper angle, and surface roughness has been analyzed through an ANOVA analysis and related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…Among these parameters, traverse speed has a great effect on the material removal rate (MRR) and surface finish of the workpiece, as surface roughness increased with an increase in traverse speed or feed rate [16,18]. In addition, Alberdi et al [19] reported that a significant increase in traverse feed rate caused an increase in both kerf taper angle and surface roughness. The taper angle decreased with an increasing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Among these parameters, traverse speed has a great effect on the material removal rate (MRR) and surface finish of the workpiece, as surface roughness increased with an increase in traverse speed or feed rate [16,18]. In addition, Alberdi et al [19] reported that a significant increase in traverse feed rate caused an increase in both kerf taper angle and surface roughness. The taper angle decreased with an increasing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Waterjets are categorized into pulsed waterjets [6], abrasive waterjets [7], cavitating waterjets [8], rotating waterjets [9], and so on. Among them, pulsed waterjets, which can improve cutting efficiency because of the water-hammer effect, have attracted the interest of researchers [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, both the heterogeneity of the material and the abrasive behaviour of the carbon fibre negatively affect the tool life. Therefore, machining conditions and tool geometry must be adapted to these materials in order to reduce tool wear and thermal and mechanical defects produced during the cutting process, such as delamination or thermal damage to the composite matrix [9,10]. On the other hand, aluminium alloys tend to modify the geometry of the tool [11], especially by the development of adhesive phenomena such as Build Up Layer (BUL) or Build Up Edge (BUE) [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, some authors have conducted studies of machining stacks with unconventional technologies such as laser or Abrasive Water Jet Machining (AWJM) [10,[14][15][16][17]. In particular, AWJM has been widely studied as one of these machining alternatives, especially to replace contour milling processes [2,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation